2019
DOI: 10.1016/j.ijppaw.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of Trypanosoma spp. detected from striped leaf-nosed bats (Hipposideros vittatus) in Zambia

Abstract: Bat trypanosomes consist of more than 30 trypanosome species from over 70 species of bats. Recent studies suggest that bats play a role in disseminating trypanosomes from African continent to the terrestrial mammals both in the Afrotropic-Palearctic Ecozones and Nearctic Ecozone. However, the diversity, distribution, and evolution of bat trypanosomes are still unclear. To better understand their evolution, more genetic data of bat trypanosomes from a variety of locations are required. During a survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This occurrence coincides with the discovery of a related species of T. dionisii (Trypanosoma sp. sequences type 2) that was detected in Zambia and infecting another bat species, Hipposideros vittatus (Qiu et al, 2019).…”
Section: Increased Phyletic Diversity Within T Dionisii T Vespertilionis and T Livingstoneimentioning
confidence: 99%
“…This occurrence coincides with the discovery of a related species of T. dionisii (Trypanosoma sp. sequences type 2) that was detected in Zambia and infecting another bat species, Hipposideros vittatus (Qiu et al, 2019).…”
Section: Increased Phyletic Diversity Within T Dionisii T Vespertilionis and T Livingstoneimentioning
confidence: 99%
“…In a previous study, Trypanosoma sp. from H. vittatus was found to be clustered with T. conorhini (Qiu et al ., 2019). The current findings, on the contrary, revealed that Trypanosoma sp.…”
Section: Discussionmentioning
confidence: 99%
“…Th_2 and Trypanosoma sp. Nandoum1 from Nandinia binotata from Cameroon (African palm civet) (Hamilton et al ., 2009; Qiu et al ., 2019). It remains unclear how palm civet trypanosome falls within the T. cruzi clade, which is dominated by bat trypanosomes.…”
Section: Discussionmentioning
confidence: 99%